2010
DOI: 10.1007/s11999-010-1491-5
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Randomized Trial of Mini-incision Posterior and Two-incision Total Hip Arthroplasty

Abstract: Background The two-incision approach to THA has been controversial, with some authors reporting its use is associated with a rapid recovery whereas others report no differences in outcomes and a higher risk of perioperative complications secondary to increased surgical complexity. Questions/purposes We therefore compared early postoperative variables including pain, length of stay, functional recovery, complications, and complexity of the mini-posterior and two-incision approaches to THA. Patients and Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 22 publications
(51 reference statements)
0
31
0
Order By: Relevance
“…The second method to determine mini-incision positioning depends on precise palpation of the greater trochanter. Many authors rely solely on the protrusion of the greater trochanter to start their skin incision, while others associate it with oblique angles varying between 10 and 45° [24][25][26][27][28][29][30][31][32][33]. However, in patients with a large amount of subcutaneous fat at the greater trochanter level, palpation can be difficult or even imprecise.…”
Section: Discussionmentioning
confidence: 99%
“…The second method to determine mini-incision positioning depends on precise palpation of the greater trochanter. Many authors rely solely on the protrusion of the greater trochanter to start their skin incision, while others associate it with oblique angles varying between 10 and 45° [24][25][26][27][28][29][30][31][32][33]. However, in patients with a large amount of subcutaneous fat at the greater trochanter level, palpation can be difficult or even imprecise.…”
Section: Discussionmentioning
confidence: 99%
“…One study included 3 patients with rheumatoid arthritis [20] and one study included 4 patients with post-traumatic arthritis [39]. Six different surgical approaches were used: anterior (Smith Petersen) [40], anterior minimally invasive [40], lateral/transgluteal (Hardinge/Bauer) [40], posterolateral [41], posterior (Moore/the southern exposure) [40], minimally invasive posterior (miniposterior) [42], and anterolateral (Watson Jones) with or without trochanteric osteotomy [40] (Table 1). The posterior approach was the most common used in 5 studies [12,13,18,21,26].…”
Section: Study Characteristics and Patient Populationsmentioning
confidence: 99%
“…On the contrary, a randomized cadaver trial revealed that significantly more muscle mass is damaged by the passage of the rasps and stem during preparation and implantation with the two-incision method versus the mini-posterior technique (gluteus medius, 15.4 vs. 4.7 %, p  = 0.0046; gluteus minimus 17.37 vs. 8.62 %, p  = 0.002) [5]. A prospective randomized trial comparing the two-incision and mini-incision posterior procedures did not reveal differences in perioperative outcomes between these two approaches [6]. Alecci et al [7] compared intra- and perioperative outcomes in patients undergoing surgery with the minimally invasive direct anterior approach or the standard lateral approach, and reported that the minimally invasive approach provided better perioperative outcomes.…”
Section: Tissue-sparing Surgerymentioning
confidence: 99%